Praescriptio Surat 3 Yohanes: Sebuah Kepedulian terhadap Kesehatan Mental Hamba Tuhan - John Marlin (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2024)
This study raises biblical and psychological aspects to show that the praescriptio of the Letter of 3 John in verses 1-2 is the foundation for concern for the mental health of God's servants. This is because discussions about the mental health of pastors as servants of God often do not receive adequate attention both in the academic realm and in the church itself, even though the facts show the vulnerability of God's servants to this issue. This study uses a word study and literature review approach as the main methods to explore the concept of mental health in the context of God's servants. The results show that the letter of 3 John, especially in verses 1-2, emphasizes the importance of mental health as a crucial foundation for the spirituality and hospitality of God's servants; as expressed in verses 3-4, which show the behavior of truth in everyday life and are reflected in verses 5-8, where the practice of hospitality is praised as part of the testimony of faith.